The New Rules on Bank Remuneration Policies Reception by the Three Major Italian Banking Groups - Gaizo, Angela; Risaliti, Gianluca; Rotili, Marco (European Scientific Journal, ESJ, 2018)
The compensation and incentive systems of executive directors have been the subject of particular attention by scholars and regulators for their sig-nificant implications on an economic and social level. Especially in the after-math of the Global Financial Crisis of 2007, compensation practices based on short-term profits were accused of having significantly increased the risk-tak-ing that threatened the global financial system. In order to avoid this repercus-sion, the European Community and Italian regulators issued instruments for encouraging banks to implement remuneration systems complying more with their operational and dimensional characteristics. The last of these rules in the Italian legal framework was the VII Update of “Circolare N° 285 of 17th De-cember 2013” which examines the new rules about the remuneration of bank-ers and executives in the Italian financial sector, and the impact of these rules on the three Italian larger significant banks. Results show that the three Italian banks have not been strongly impacted by these rules. Since 2013, in fact, the remuneration system of the three banking groups examined were characterized by a proper balancing between the fixed and the variable component of remu-neration, as well as by a binding (ex-ante and ex-post) adjusting system. Above all, the new rules have affected the number of the “material risk-tak-ers”, which increased in 2015.